Interaction Between Treatment and Age or Sex in Non-ST-Segment Elevation Acute Coronary Disease and Three-Vessel Disease - Li, Tianyu; Jiang, Lin; Xu, Lianjun; Tian, Jian; Zhao, Xueyan; Feng, Xinxing; Wang, Dong; Zhang, Yin; Sun, Kai; Xu, Jingjing; Liu, Ru; Xu, Bo; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aims: To explore the effects of age and sex on outcomes of coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI) in non-ST-segment elevation acute coronary syndrome (NSTE-ACS) patients with three-vessel disease (TVD). Methods and Results: The study is a subanalysis of data from a prospective cohort of 8,943 patients with angiographical confirmed TVD at Fuwai Hospital, Chinese Academy of Medical Sciences, Beijing, China. The primary endpoint was major adverse cardiac and cerebrovascular events (MACCE), a composite of all-cause death, myocardial infarction and stroke. 2,819 NSTE-ACS patients receiving CABG (43.6%) or PCI (56.4%) were included, among whom 32.7% were 65-74 years, 7.2% were ≥75 years, and 22.6% were women. Median follow-up duration was 6.8 years. The superiority of CABG relative to PCI in terms of MACCE decreased with age (adjusted hazard ratio [HR] [95% confidence interval (CI)]: <65 years: 0.662 [0.495-0.885], p=0.005; 65-74 years: 0.700 [0.512-0.956], p=0.025; ≥75 years: 0.884 [0.529-1.479], p=0.640), and was only seen in men (adjusted HR [95% CI]: men: 0.668 [0.526-0.848], p=0.001; women: 0.713 [0.505-1.006], p=0.054). Significant treatment-by-sex and treatment-by-age interactions were observed in patients ≥75 years and in women, respectively (pinteraction with sex=0.001; pinteraction with age=0.002). Conclusions: CABG is favorable for most NSTE-ACS patients with TVD. The preponderance of CABG over PCI disappeared in patients ≥75 years and women. PCI is superior in women ≥75 years.